Synthesis of the Antimicrobial Peptide Murepavadin Using Novel Coupling Agents - Júlia García-Gros; Yolanda Cajal; Ana Maria Marqués; Francesc Rabanal (Biomolecules, 2024)
The problem of antimicrobial resistance is becoming a daunting challenge for human society and healthcare systems around the world. Hence, there is a constant need to develop new antibiotics to fight resistant bacteria, among other important social and economic measures. In this regard, murepavadin is a cyclic antibacterial peptide in development. The synthesis of murepavadin was undertaken in order to optimize the preparative protocol and scale-up, in particular, the use of new activation reagents. In our hands, classical approaches using carbodiimide/hydroxybenzotriazole rendered low yields. The use of novel carbodiimide and reagents based on OxymaPure® and Oxy-B is discussed together with the proper use of chromatographic conditions for the adequate characterization of peptide crudes. Higher yields and purities were obtained. Finally, the antimicrobial activity of different synthetic batches was tested in three Pseudomonas aeruginosa strains, including highly resistant ones. All murepavadin batches yielded the same highly active MIC values and proved that the chiral integrity of the molecule was preserved throughout the whole synthetic procedure.